Hydrochar production from high-ash low-lipid microalgal biomass via hydrothermal carbonization: Effects of operational parameters and products characterization - Khoo, C.G. (Academic Press Inc., 2020)
This study aims to produce hydrochar from high-ash low-lipid Chlorella vulgaris biomass via hydrothermal carbonization (HTC) process. The effects of hydrothermal temperature and retention time with respect to the physicochemical properties of hydrochar were studied in the range of 180â250 Â°C and 0.5â4 h, respectively. It was found that the hydrothermal temperature had resulted in a significant reduction of hydrochar yield as compared to the retention time. The raw microalgal biomass was successfully converted into an energy densified hydrochar via an optimized HTC reaction, with higher heating value (HHV) of 24.51 kJ/g, which was approximately two-times higher than that of raw biomass. In addition, the overall carbon recovery rate and energy yield were in the range of 53.2â86.4 and 46.9â76.6, respectively. The high quality of the produced hydrochar was further supported by the plot of van Krevelen diagram and combustion behaviour analysis. Besides, the aqueous phase collected from HTC process could be further used as nutrients source to cultivate C. vulgaris, in which up to 70 of the biomass yield could be attained as compared to the control cultivation condition. The reusability of the aqueous phase collected from HTC process as an alternative nutrients source to cultivate microalgal indicated the feasibility and positive integration of HTC process in microalgal biofuel processing chain. Â© 2020 Elsevier Inc.